The “Inverse” Seasonal Blood Pressure Variability Phenotype - V. M. Gorbunov; M. I. Smirnova; Y. N. Koshelyaevskaya; N. N. Panueva; N. V. Furman; P. V. Dolotovskaya (Рациональная фармакотерапия в кардиологии, 2021)
The seasonal blood pressure variability (BPV) is known to demonstrate a typical winter peak. Recently, more attention is paid to the opposite situation: the summer BP levels being higher than those in winter. This phenomenon is called inverse BPV. The present article summarizes recent data on this topic. The data of the HOMED-BP project, as well as the results of the original prospective study in 770 hypertensive patients from two Russian Federation regions (mean follow-up duration 6.4 years), were used. According to the preliminary knowledge, the prevalence of inverse BPV in hypertensive patients is relatively high (15-25%). This phenomenon is more typical for treated patients, particularly for those on combination therapy, and is associated with beta-blocker intake. Higher duration of hypertension and higher levels of some risk factors (smoking) characterize the patients with inverse BPV. According to the HOMED-BP data, patients with inverse BPV had the highest overall cardiovascular risk (hazard ratio in comparison with the reference group of “minimal” “normal” BPV was 3.07; p=0.004). In summary, inverse BPV is a potentially unfavorable BP phenotype. However, its reproducibility and prospective value deserve further investigation. The absolute magnitude of seasonal BPV in these patients, calculated using different BP measurement methods, warrants special attention.